The Mechanism of Synchronous Precise Regulation of Two Shrimp White Spot Syndrome Virus Targets by a Viral MicroRNA - He, Yaodong; Ma, Tiantian; Zhang, Xiaobo (Frontiers in Immunology, 2017)
MicroRNAs (miRNAs), important factors in animal innate immunity, suppress the expressions of their target genes by binding to 3’ untranslated regions (3’UTRs) of target mRNAs. However, the mechanism of synchronous regulation of multiple targets by a single miRNA remains unclear. In this study, the interaction between a white spot syndrome virus (WSSV) miRNA (WSSV-miR-N32) and its two viral targets (wsv459 and wsv322) was characterized in shrimp. The results indicated that the viral WSSV-miR-N32 significantly inhibited virus infection by simultaneously targeting wsv459 and wsv322. The silencing of wsv459 or wsv322 by siRNA led to significant decrease of WSSV copies in shrimp, showing that the two viral genes were required for WSSV infection. WSSV-miR-N32 could mediate 5’-3’ exonucleolytic digestion of its target mRNAs, which stopped at the sites of target mRNA 3’UTRs close to the sequence complementary to the miRNA seed sequence. The complementary bases (to the target mRNA sequence) of a miRNA 9th-18th non-seed sequence were essential for the miRNA targeting. Therefore our findings presented novel insights into the mechanism of miRNA-mediated suppression of target gene expressions, which would be helpful for understanding the roles of miRNAs in innate immunity of invertebrate.